Geomorphological Analysis and Morphometric Characteristics of Wadi Jarjir Using Remote Sensing and Geographic Information Systems (GIS) - طارق المبروك البكوش; محمد الطاهر ميلاد (African Journal of Advanced Pure and Applied Sciences, 2025)
This study examines the morphometric characteristics and their geomorphological implications for Wadi Jirjir, which is considered one of the semi-arid valleys in northwestern Libya. The upper course of Wadi Jirjir originates on the northwestern slopes of the Western Mountain and extends north to south until it reaches Senawan near the Tunisian border. The wadi suffers from the scarcity of surface water, with significant fluctuations from year to year. The analysis of the morphometric characteristics was based on Geographic Information Systems (GIS), using ArcMap 10.8 and digital elevation data obtained from the United States Geological Survey (USGS), with a spatial resolution of 30 meters. The study aimed to delineate the drainage basin and stream network from the DEM using GIS techniques, develop a morphometric database for the wadi, and produce a series of thematic maps derived from this database. One of the key findings of the study is the geomorphological youth of the basin, as indicated by the high relief ratio, which reached 2.7 m/km. The study recommends the use of modern geospatial technologies, particularly GIS, in morphometric analyses, along with high-resolution digital elevation models. It also emphasizes the importance of developing comprehensive geographic databases to support decision-making and planning standards for various services, enabling GIS specialists to apply spatial suitability analyses effectively.